Sources on the history of Kazakhstan (Journal of history, 2020)
The modern historical science of Kazakhstan pays special attention to the development problems of sources and methods of historical research, since without the involvement of the scientific revolution in the new historical sources, it is impossible to improve the quality and efficiency of historical research. To research the history of Kazakh Khanate is relevant today and is determined, firstly, increasing interest of the history of the origins of Kazakh statehood in connection with the acquisition of independence by Kazakhstan, which created this historical basis. The relevance of the study is determined by practical necessity in historical science introduction to the scientific revolution of original sources containing valuable factual material on the history of Kazakh Khanate. To restore the historic picture of the past is necessary to attract the many, often contradictory, and diverse sources of facts and data that we receive from various sources, first and foremost – written records. This article discusses the written monuments XV-XVII centuries, started in Central Asia and contain the most complete and valuable information on the history and culture of the Kazakh people. It has a rich historical literature in Oriental languages, which reflected the centuries-old history of Kazakhstan. Written monuments of Central Asia are important and valuable to study the history of the Kazakh people.Key words: source, theory, classification, principle, method.